Natural hazards in Costa Rica: an approach from Social Studies and Civic Education. - Zúñiga Arias, Ana Yolanda (2015)
This article, research is derived from “Hurricanes in Costa Rica: agro-ecological impact and social risk, 1970-2010”, by Yolanda Zúñiga and Rafael Ledezma in the School of History at the National University. Analyzes the natural hazards in Costa Rica caused by weather phenomena with the objective of providing information and educational activities that can be applied in the lessons of Social Studies and Civics. The research includes the use of books about risk and vulnerability, laws and decrees, reports of the National Emergency Commission and newspaper articles. The article aims to contribute to the consolidation of citizenship ready for the impact caused by natural phenomena in Costa Rican society.